MODIFICAÇÃO DE FILTROS DE CIGARROS CONTRABANDEADOS COM ÍONS FÉRRICOS PARA UTILIZAÇÃO NA DEGRADAÇÃO DE CORANTES REATIVOS. - Felipe, Letícia Polli Glugoski (2016)
This paper describes a study of two serious environmental problems, filters of smuggled cigarettes and dyes from the textile industry. Immobilized ferric ions in filters of smuggled cigarettes, in order to develop a new material, to act as a catalyst in the degradation of the dye Reactive Black 5, through advanced oxidation process photo- Fenton. For characterization of the material used up techniques such as spectroscopy in the infrared spectroscopy, diffuse reflectance in the UV-Vis region, scanning electron microscopy coupled with energy dispersive and atomic absorption, it was found that the iron is immobilized on the surface of the material evenly and that the structure of the material is not modified after being used in various degradations of the dye Reactive Black 5. The 23 factorial design showed that the best conditions for dye degradation were obtained using 1g of material, 100 mg L-1 H2O2 and pH 3. The material showed excellent performance, reducing 97.68% of the chromophore of the dye grouping in 60 minutes of reaction. At pH 7 the discoloration was 72.67%, not observing formation of precipitates. The material was reused in 9 dye treatments, demonstrating an excellent catalytic potential and the amount of leached ferric ions fell below 3 mgL-1.The material was also tested in the degradation of a real effluent, reducing 70, 57% of the total organic carbon in 120 minutes of reaction. This work contributed to the solution of contraband cigarette filters and textile dyes, since the results obtained were effective compared with other materials used in the decolorization of dyes through the photo-Fenton process.